FES-UPP: A Flexible Functional Electrical Stimulation System to Support Upper Limb Functional Activity Practice - Sun, Mingxu; Smith, Christine; Howard, David; Kenney, Laurence; Luckie, Helen; Waring, Karen; Taylor, Paul; Merson, Earl; Finn, Stacey (Frontiers in Neuroscience, 2018)
There is good evidence supporting highly intensive, repetitive, activity-focused, voluntary-initiated practice as a key to driving recovery of upper limb function following stroke. Functional electrical stimulation (FES) offers a potential mechanism to efficiently deliver this type of therapy, but current commercial are too inflexible and/or insufficiently automated, in some cases requiring engineering support. In this paper, we report a new, flexible upper limb FES system, FES-UPP, which addresses the issues above. The FES-UPP system consists of a 5-channel stimulator running a flexible FES finite state machine (FSM) controller, the associated setup software that guides therapists through the setup of FSM controllers via five setup stages, and finally the session manager used to guide the patient in repeated attempts at the activities(s) and provide feedback on their performance. The FSM controller represents a functional activity as a sequence of movement phases. The output for each phase implements the stimulations to one or more muscles. Progression between movement phases is governed by user-defined rules. Three therapists used the FES-UPP system to set up FES-supported activities with two patient participants with severely impaired upper-limbs. Therapists used the system in their usual clinical settings, without engineering support. Six different functional activities, tailored to suit the upper limb impairment levels of each participant were used, over 7 sessions of FES-supported therapy per participant. The efficiency of delivery of the therapy using FES-UPP was promising when compared with published data on traditional face-face therapy For example, in the last session participant 1 completed 19.4 minutes practice out of 25.8 minutes therapy time and in this time achieved 98 successful repetitions; participant 2 completed 16.3 minutes practice out of 21.7 minutes and 100 successful repetitions. The FES-UPP system described in this paper has been shown to allow therapists with no engineering support to set up state-machine FES controllers bespoke to the patient’s impairment patterns and activity requirements. The case studies demonstrated that the system can be used to efficiently deliver high intensity, activity-focused therapy. Nevertheless, further work to reduce setup time is still required.